The Philosophical Meaning of Batak Toba "Naso Matanggak Di Hata, Naso Matahut Di Bohi", A Study of Character Education - Siahaan, Renson; Zega, Yunardi Kristian; Situmeang, Tri Murni (Educative: Jurnal Ilmiah Pendidikan, 2023)
The Batak’ tribe is famous for its customs that are thick with a wealth of life philosophies. Batak’ people uphold the noble values that become these traditions. One of the philosophies taught for generations by parents to their children is: "Naso matanggak di Hata, naso matahut di bohi". The sentence has the meaning of daring to say right and wrong. The aims of this research are to describe the philosophy of Toba Batak’ culture Naso Matanggak Di Bohi, Naso Matahut Di Hata, towards the character education of children as the next generation. The Method used in this research is descriptive with a literature study approach. The Result of this research is the person will dare to appear different and firm with principles. With the philosophy that has been passed down from Batak’ ancestors, children as the next generation of the nation can understand the meaning implied in it and learn a good lesson. This paper can be a useful contribution for anthropologists as a reference in exploring and understanding the philosophy of Toba Batak’ culture in character education for organization, society and socializing with others.